The Influence of Brand Image and Lifestyle on Purchase De-cisions: a Case Study of Specs Footwear Users at Universi-tas Medan Area - Tegar Sry Restu’eli Gulo; Muhammad Yamin Siregar (INFOKUM, 2025)
This research aims to analysed the influence of brand image and lifestyle on pur-chase decisions among Specs footwear users at Universitas Medan Area. The study ap-plies a quantitative method using a survey approach. Data were collected through ques-tionnaires distributed to 100 respondents who are active students and users of Specs footwear. The results of the analysis show that brand image has a significant positive influence on purchasing decisions. Likewise, lifestyle also has a significant effect on con-sumer behaviour in choosing Specs products. Simultaneously, brand image and lifestyle jointly contribute significantly to the decision-making process. These findings indicate that both variables are important considerations for companies in formulating marketing strategies that are aligned with consumer perceptions and lifestyles. This research con-cludes that enhancing brand image and understanding consumer lifestyle are key factors in increasing purchasing decisions.